(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Tuberculosis (TB) remains one of the leading infectious causes of morbidity and mortality worldwide. The clinical course and severity of tuberculosis infection in adults are determined not only by the virulence of Mycobacterium tuberculosis (Mtb) but also by the host immune response. The present study aims to analyze key immunological indicators in adults with pulmonary tuberculosis and to evaluate their association with disease severity. A comprehensive assessment of cellular and humoral immune parameters, cytokine profiles, and inflammatory biomarkers was performed in adult patients with varying degrees of disease severity. The findings demonstrate that severe forms of tuberculosis are characterized by pronounced alterations in T-lymphocyte subpopulations, increased pro-inflammatory cytokine levels (TNF-α, IL-6, IFN-γ), elevated acute-phase reactants, and evidence of immune dysregulation. The imbalance between protective cellular immunity and excessive inflammatory response appears to play a central role in disease progression. These results underline the importance of immunological monitoring in tuberculosis management and provide insights into prognostic markers and potential immunomodulatory therapeutic strategies.